2021
DOI: 10.3390/cells10030663
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 Channels Contribute to the Regulation of Human Atrial Fibroblast Mechanical Properties and Matrix Stiffness Sensing

Abstract: The mechanical environment of cardiac cells changes continuously and undergoes major alterations during diseases. Most cardiac diseases, including atrial fibrillation, are accompanied by fibrosis which can impair both electrical and mechanical function of the heart. A key characteristic of fibrotic tissue is excessive accumulation of extracellular matrix, leading to increased tissue stiffness. Cells are known to respond to changes in their mechanical environment, but the molecular mechanisms underlying this ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…Over-expression and siRNA studies revealed that Piezo1 positively affected stiffness of a human atrial fibroblast cell line, including increasing the amount, thickness and organization of the F-actin network. Moreover, Piezo1 overexpressing cells could confer increased stiffness to neighbouring non-transfected cells through a paracrine IL-6 signalling mechanism [228]; similar to that identified in our recent study [134].…”
Section: Piezo1 In Cardiac Fibroblastssupporting
confidence: 83%
See 1 more Smart Citation
“…Over-expression and siRNA studies revealed that Piezo1 positively affected stiffness of a human atrial fibroblast cell line, including increasing the amount, thickness and organization of the F-actin network. Moreover, Piezo1 overexpressing cells could confer increased stiffness to neighbouring non-transfected cells through a paracrine IL-6 signalling mechanism [228]; similar to that identified in our recent study [134].…”
Section: Piezo1 In Cardiac Fibroblastssupporting
confidence: 83%
“…While Piezo1 was directly activated by stretch, mechanical induction of BKCa activity was secondary to calcium influx via Piezo1, suggesting interplay between these channels in human atrial fibroblasts [ 69 ]. Another recent report from the same group described a role for Piezo1 in increasing atrial fibroblast cell stiffness in response to increased ECM stiffness [ 228 ]. Over-expression and siRNA studies revealed that Piezo1 positively affected stiffness of a human atrial fibroblast cell line, including increasing the amount, thickness and organization of the F-actin network.…”
Section: Piezo1 Channelmentioning
confidence: 99%
“…Of note, the stiffness of fibrotic myocardium is estimated at 20-100 kPa [51][52][53]. It has also been shown previously that Piezo1 reacts to stiffness, in both stem cells [54] and atrial fibroblasts [55].…”
Section: Discussionmentioning
confidence: 70%
“…The mechanical properties of the AJP samples were characterised using a Chiaro nanoindenter (Optics11). This system and its sister system, the Piuma, are emerging tools for measuring the mechanical properties of hydrogels and for mechanobiology [ 40 , 41 , 42 ]. Both are comprised of a spherical indenter on a cantilever of known stiffness, the deflection of which is measured by interferometry via a ferrule-topped optical fiber [ 43 ].…”
Section: Methodsmentioning
confidence: 99%